A novel, simple near-infrared thoracoscopic technique by a particular route for locating lung nodules - Li, Zhengjun; Xia, Mozhu; Liu, Chang; Xie, Liwei; Wang, Tao; Ren, Yi (Frontiers in Oncology, 2023)
Background The localization of pulmonary nodules prior to thoracoscopic surgery remains challenging for thoracic surgeons, especially for those nodules that are not visible or palpable on the lung surface. Our study is a simple and effective minimally invasive method using indocyanine green through a special pathway to locate pulmonary nodules and fluorescence thoracoscopic surgery. Methods Thoracoscopic surgery was performed for 18 undiagnosed peripheral non-solid nodules no larger than 2 cm after location. After 0.3 mg/kg indocyanine green was injected through the peripheral vein, the puncture needle was pulled out after it reached approximately 1 cm of the pulmonary parenchyma near the nodules. This was followed by transfer to the operating room. The nodule was initially localized by using a near-infrared thoracoscope to visualize indocyanine green fluorescence. Then, thoracoscopic resection was performed. Results Eighteen patients received this special and simple localization method, and underwent near-infrared, image-guided, video-assisted thoracoscopic surgery resection. Median computed tomography (CT) tumor size was 1.2 cm. Median depth from the pleural surface is 1.6 cm (range, 0.1–4.6 cm). The median time of CT-guided intervention was 12 min. The duration of thoracoscopic surgery was 67 min. Indocyanine green fluorescence was clearly identified in 17 of 18 patients (94.4%). The surgical margins were all negative on final pathology. The final diagnoses included 17 primary lung cancers, and 1 benign lung tumor. Conclusions CT-guided single puncture of indocyanine green after peripheral intravenous injection is a simple, effective, and safe method to locate the nodule. This offers surgeons the ease of localization through direct indocyanine green fluorescence imaging, and it can be used as an effective alternative to other placement methods of locating pulmonary nodules.